Cocktail of isobavachalcone and curcumin enhance eradication of Staphylococcus aureus biofilm from orthopedic implants by gentamicin and alleviate inflammatory osteolysis - Chen, Yan; Hu, Hao; Huang, Fangli; Ling, Zemin; Chen, Bolin; Tan, Bizhi; Wang, Tingxuan; Liu, Xiao; Liu, Chun; Zou, Xuenong (Frontiers in Microbiology, 2022)
Orthopedic device-related infection (ODRI) caused by Staphylococcus aureus, especially methicillin-resistant S. aureus (MRSA) biofilm may lead to persist infection and severe inflammatory osteolysis. Previous studies have demonstrated that both isobavachalcone and curcumin possess antimicrobial activity, recent studies also reveal their antiosteoporosis, anti-inflammation, and immunoregulatory effect. Thus, this study aims to investigate whether the combination of isobavachalcone and curcumin can enhance the anti-S. aureus biofilm activity of gentamicin and alleviate inflammatory osteolysis in vivo. EUCAST and a standardized MBEC assay were used to verify the synergy between isobavachalcone and curcumin with gentamicin against planktonic S. aureus and its biofilm in vitro, then the antimicrobial and immunoregulatory effect of cocktail therapy was demonstrated in a femoral ODRI mouse model in vivo by μCT analysis, histopathology, quantification of bacteria in bone and myeloid-derived suppressor cell (MDSC) in bone marrow. We tested on standard MSSA ATCC25923 and MRSA USA300, 5 clinical isolated MSSA, and 2 clinical isolated MRSA strains and found that gentamicin with curcumin (62.5–250 μg/ml) and gentamicin with isobavachalcone (1.56 μg/ml) are synergistic against planktonic MSSA, while gentamicin (128 μg/ml) with curcumin (31.25–62.5, 250–500 μg/ml) and gentamicin (64–128 μg/ml) with isobavachalcone (1.56–12.5 μg/ml) exhibit synergistic effect against MSSA biofilm. Results of further study revealed that cocktail of 128 μg/ml gentamicin together with 125 μg/ml curcumin +6.25 μg/ml isobavachalcone showed promising biofilm eradication effect with synergy against USA300 biofilm in vitro. Daily intraperitoneal administration of 20 mg/kg/day isobavachalcone, 20 mg/kg/day curcumin, and 20 mg/kg/day gentamicin, can reduce inflammatory osteolysis and maintain microarchitecture of trabecular bone during orthopedic device-related MRSA infection in mice. Cocktail therapy also enhanced reduction of MDSC M1 polarization in peri-implant tissue, suppression of MDSC amplification in bone marrow, and Eradication of USA300 biofilm in vivo. Together, these results suggest that the combination of isobavachalcone and curcumin as adjuvants administrated together with gentamicin significantly enhances its antimicrobial effect against S. aureus biofilm, and can also modify topical inflammation in ODRI and protect bone microstructure in vivo, which may serve as a potential treatment strategy, especially for S. aureus induced ODRI.